387 Polyunsaturated Fatty Acids in Colostrum and Cognitive Development in Breastfed Children of the Eden Mother-Child Cohort Study. (October 2012) - Bernard, JY; Agostini, M de; Forhan, A; Garcia, C; Armand, M; Bonet, M; Marchand, L; Blondel, B; Champion, V; Kaminski, M; LauzonGuillain, B de; Charles, MA; et al.
Abstract : Background and Aims: Epidemiological studies suggest that breastfeeding could be beneficial for child cognitive development, but pathways involved remain to be elucidated. We aimed to investigate the potential role of breast milk content in polyunsaturated fatty acids (PUFAs), by studying their associations with later cognitive development. Methods: We analyzed lipid contents of colostrum samples collected from 613 breastfeeding mothers of the EDEN mother-child cohort. Cognitive development at 3 years was assessed with the Ages and Stages Questionnaire (ASQ, score between 0 and 300). We investigated associations between colostrum PUFAs and ASQ score using multiple linear regressions adjusted for centre, child's age, gender and gestational age, maternal tobacco and alcohol consumptions, parental education, siblings, caregivers, preschool attendance and exclusive breastfeeding duration. Results: Mean ASQ score was 274.2 (±25.1). Total PUFAs and n -6 PUFAs means were respectively 14.3% (±2.0) and 12.1% (±1.9) of total lipids in colostrum. Mean n -6/ n -3 ratio was 5.7 (±1.3). After adjustment, ASQ score was negatively associated with total PUFAs (β= –1.8 [–2.8; –0.8]), n -6 PUFAs (–1.95 [–3.0; –0.9]) and n -6/ n -3 ratio (–1.7 [–3.3; –0.2]). No association was found with n -3 PUFAs. Associations did not differ according to breastfeeding duration ( P interaction >0.57). Conclusions: After adjustment for confounders, especially maternal education, colostrum content in n -6 PUFA was negatively associated with child cognitive development, independently of exclusive breastfeeding duration. These results suggest that n -6 PUFAs provided in excess might compete with n -3 PUFAs biosynthesis necessary for early brain maturation and impact negatively on later cognitive development.